Early-age behaviour of cement-based self-leveling flooring compounds - Kucharczyková, Barbara; Kocáb, Dalibor (IOP Publishing, 2018)
The article deals with the cement-based flooring compounds, especially with the behaviour during the early solidification process. A touch-less laser sensor and a cone-shaped mould were used for the measurement of the plastic settlement/shrinkage. The process of solidification and the strength development were determined using the ultrasonic pulse velocity measurement. Both test devices were equipped with the thermocouple to measure the real-time internal temperature evolution during solidification of the flooring compounds. The measurements presented in this paper proved to be useful for the clarification of the technological problems which arose during the manufacturing of the test specimens.

The article deals with the cement-based flooring compounds, especially with the behaviour during the early solidification process. A touch-less laser sensor and a cone-shaped mould were used for the measurement of the plastic settlement/shrinkage. The process of solidification and the strength development were determined using the ultrasonic pulse velocity measurement. Both test devices were equipped with the thermocouple to measure the real-time internal temperature evolution during solidification of the flooring compounds. The measurements presented in this paper proved to be useful for the clarification of the technological problems which arose during the manufacturing of the test specimens.
Early-age behaviour of cement-based self-leveling flooring compounds
Keywords: Flooring compound; shrinkage; early solidification; ultrasonic pulse velocity; temperature; Flooring compound; shrinkage; early solidification; ultrasonic pulse velocity; temperature